2020
DOI: 10.1200/jco.2020.38.15_suppl.6516
|View full text |Cite
|
Sign up to set email alerts
|

Combination of monalizumab and cetuximab in recurrent or metastatic head and neck cancer patients previously treated with platinum-based chemotherapy and PD-(L)1 inhibitors.

Abstract: 6516 Background: Monalizumab is a first-in-class immune checkpoint inhibitor targeting Natural Killer Group 2A (NKG2A), which is expressed on subsets of Natural Killer (NK), gd T and tumor-infiltrating CD8+T cells. NKG2A blockade promotes innate anti-tumor immunity mediated by NK and CD8+T cells and enhances NK cell antibody-dependent cell-mediated cytotoxicity induced by cetuximab. In a Phase I study, the combination of monalizumab and cetuximab was well tolerated. In an initial expansion cohort 1 of 40 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…The combination of monalizumab and cetuximab has been studied in a multi-centric phase Ib-II trial (NCT02643550), the results of the phase II cohort concerning platinum resistant patients 45% of which had received an anti-PD-(L)1 are particularly interesting [55]: over 40 patients, a rate of 27.5% of objective response is achieved with a median PFS of 4.5 months and a median survival of 8.5 months. Results of an expansion cohort concerning patients who had all been treated with platinum and immunotherapy confirm a 20% ORR with a median duration of 5.2 months [50]. These results have led to planned a phase III (INTERLINK-1) for HNSCC patients in the R/M setting pretreated with platinum and anti-PD-(L)1 randomizing cetuximab + monalizumab vs. cetuximab + placebo.…”
Section: Monalizumab and Cetuximabmentioning
confidence: 83%
“…The combination of monalizumab and cetuximab has been studied in a multi-centric phase Ib-II trial (NCT02643550), the results of the phase II cohort concerning platinum resistant patients 45% of which had received an anti-PD-(L)1 are particularly interesting [55]: over 40 patients, a rate of 27.5% of objective response is achieved with a median PFS of 4.5 months and a median survival of 8.5 months. Results of an expansion cohort concerning patients who had all been treated with platinum and immunotherapy confirm a 20% ORR with a median duration of 5.2 months [50]. These results have led to planned a phase III (INTERLINK-1) for HNSCC patients in the R/M setting pretreated with platinum and anti-PD-(L)1 randomizing cetuximab + monalizumab vs. cetuximab + placebo.…”
Section: Monalizumab and Cetuximabmentioning
confidence: 83%
“…The phase II clinical trial results of the combination of monalizumab and cetuximab, demonstrated a 30% objective response rate in immunotherapy-refractory in patients with head and neck squamous cell carcinoma compared to 12.6% in previous studies using cetuximab alone. 106 Although these results are promising, it may prove to be even more useful to generate NKG2A deficient NK cells for use in adoptive transfer since NK cells are often found in very low numbers in the TME 18 and may not effectively respond to anti-NKG2A therapy.…”
Section: Antibody-mediated Checkpoint Blockade Therapiesmentioning
confidence: 99%
“…Moreover, soluble MULT1, a high affinity mouse NKG2D ligand stimulates NKG2D in distant NK cells and enhances NK cell tumor immunity [ 106 ]. Hence, a clinically used antibody, monalizumab, has been developed targeting NKG2A, an inhibitory checkpoint of NK cells, which not only promotes NK cell function in various preclinical models, as previously characrerized, but also potentiates anti-PD-1 [ 226 ] and anti-EGFR (cetuximab) therapy [ 227 ]. In addition to antibody, NKG2A null NK cells, constructed through retroviral transduction of NKG2A blocker which inhibits de novo NKG2A expression, present increased anti-tumor activity in pre-clinical model [ 228 ].…”
Section: Introductionmentioning
confidence: 99%